Conflicts among religious people in a Catholic mission in the countryside of Goiás state in the 1950s: Resentment of Remigio Corazza in his autobiographical account - da Silva, Raylinn Barros (Revista Crítica Histórica, 2020)
The aim of this study was to uncover the conflicts that occurred between religious people inside of the Orion Catholic mission in the old extreme north of Goias state in the middle of the 20th century. One hypothesis is the possibility that these conflicts may have influenced at some point in the development of the mission. This study is the result of a bibliographical research and the source used was the memory report - autobiographical book Silence Prudent - of one of those religious members: Remígio Corazza. The methodology was based on an analysis of the work having as reference studies on autobiographies, memory and resentments. A justification for this study is the need to historicize this source that can contribute to the understanding of the Orion mission in the region by another bias: the internal conflicts among some of its members.